Kaiju no. 8. 10 - Matsumoto, Naoya, 1982- (Shonen Jump manga., 2024)
"With the highest kaiju-emergence rates in the world, Japan is no stranger to attack by deadly monsters. Enter the Japan Defense Force, a military organization tasked with the neutralization of kaiju. Kafka Hibino, a kaiju-corpse cleanup man, has always dreamed of joining the force. But when he gets another shot at achieving his childhood dream, he undergoes an unexpected transformation. How can he fight kaiju now that he's become one himself?! With kaiju cataclysms transpiring across Japan, Hoshina heads into battle equipped with Numbers Weapon 10 and soon discovers that wielding the first-ever sentient kaiju weapon won't be easy. Meanwhile, back in the Oizumi area where Kafka is, six supergiant-class kaiju emerge, worsening an already grave situation. But just as things get dire, some unexpected backup arrives!"--Back cover.